Morphological Characterization of the Diatom Pseudo-nitzschia Species (Bacillariophyceae) from Malaysian Waters - Teng, Sing Tung; Lim, Hong Chang; Leaw, Chui Pin; Lim, Po Teen (2012)
The diatom Pseudo-nitzschia has been known for domoic acid poisoning, or better known as Amnesic Shellfish Poisoning (ASP). Accumulation of domoic acid (DA) in commercial bivalves during the bloom of this toxic diatom has caused economic losses to the industry. To clarify the status of ASP and the diversity of toxic or potentially toxic Pseudo-nitzschia species in the Malaysian waters, plankton samples were collected from 17 locations using 20 µm-mesh plankton net haul. Samples were subjected to acid wash treatment before detail observation under transmission electron microscope (TEM). Identification of Pseudonitzschia species was based on the frustules morphology with the morphometric measurements. In total, 22 species were identified, including 18 new records in Malaysia. Pseudo-nitzschia brasiliana, P. caciantha, P. calliantha, P. cuspidata, P. delicatissima, P. multistriata, P. pseudodelicatissima, P. pungens and P. turgidula are known to be toxic and previously reported to associate with ASP events worldwide. This study provides useful information on the harmful algae species inventory of the country.